2023
DOI: 10.3390/s23063331
|View full text |Cite
|
Sign up to set email alerts
|

EMG-Based Estimation of Lower Limb Joint Angles and Moments Using Long Short-Term Memory Network

Abstract: One of the fundamental limitations in human biomechanics is that we cannot directly obtain joint moments during natural movements without affecting the motion. However, estimating these values is feasible with inverse dynamics computation by employing external force plates, which can cover only a small area of the plate. This work investigated the Long Short-Term Memory (LSTM) network for the kinetics and kinematics prediction of human lower limbs when performing different activities without using force plates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Consequently, LSTM is widely used owing to its capability of generating accurate outputs for time series: the action patterns of walking occur in a time series ( Song et al, 2020 ), and LSTM generates outputs based on the inputs from the past ( Greff et al, 2017 ), making it suitable for predicting joint kinematics and kinetics ( Ma et al, 2020 ). Also, the sEMG feature extraction is used widely, where features are extracted within a sliding window and used as inputs to predict joint kinetics or kinematics ( Bi et al, 2019 ; Gupta et al, 2020 ; Zhang et al, 2021 ; Chen et al, 2022 ; Rabe and Fey, 2022 ; Truong et al, 2023 ). Previous studies have shown that using sEMG features as input (e.g., Spanias et al, 2015 , 2018 ), the LSTM structure (e.g., Ren et al, 2022 ), and their combined implementations (e.g., Song et al, 2020 ) provide a successful prediction of intended motion.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, LSTM is widely used owing to its capability of generating accurate outputs for time series: the action patterns of walking occur in a time series ( Song et al, 2020 ), and LSTM generates outputs based on the inputs from the past ( Greff et al, 2017 ), making it suitable for predicting joint kinematics and kinetics ( Ma et al, 2020 ). Also, the sEMG feature extraction is used widely, where features are extracted within a sliding window and used as inputs to predict joint kinetics or kinematics ( Bi et al, 2019 ; Gupta et al, 2020 ; Zhang et al, 2021 ; Chen et al, 2022 ; Rabe and Fey, 2022 ; Truong et al, 2023 ). Previous studies have shown that using sEMG features as input (e.g., Spanias et al, 2015 , 2018 ), the LSTM structure (e.g., Ren et al, 2022 ), and their combined implementations (e.g., Song et al, 2020 ) provide a successful prediction of intended motion.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [30] observed that an LSTM model could predict lower limb joint torque during various activities accurately, with a relatively low error, using sEMG signals and joint angles as inputs. Truong et al [31] extracted several sEMG features to predict joint angles and joint torque using an LSTM model when squatting, picking up an object, and sitting-standing.…”
Section: Introductionmentioning
confidence: 99%